Penciling, inking, and coloring your graphic novel - Lee, Frank, 1980- (Lee, Frank, 1980- How to draw your own graphic novel (PowerKids Press), 2012)
This guide teaches readers important techniques and encourages them to use their imaginations. Each step in creating graphic novel art is explained from beginning with pencil to ending.